The making of Gratian's Decretum - Winroth, Anders (Cambridge studies in medieval life and thought, 2000)
Gratian's Decretum was a key text in the legal and intellectual developments of the twelfth century, and long remained a fundamental work. Professor Winroth has now discovered the shorter, original version of the Decretum, which invites a reconsideration of the resurgence of law in the twelfth century.